The diagnosis of traumatic epiphyseolysis in the distal radial bone without any displacement - Shevchenko, Stanislav; Martyuk, Victor; Yakovenko, Inna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The diagnosis of traumatic distal epiphysiolysis of the radial bone “without epiphyseal dislocation” was made with use of the clinical, radiological and ultrasonographic methods in 15 patients. The ultrasonographic examination was performed with a real-time Sonoline G50 scanner (Siemens), equipped with a linear transducer, whose oscillation frequency was 5-10 MHz. The scanning was made in two (transverse and longitudinal) projections at rest. A technique of ultrasonographic examination was elaborated and the ultrasonographic semiotics for cases of traumatic distal epiphysiolysis of the radial bone “without epiphyseal dislocation” was described.